1998
DOI: 10.1159/000008569
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Omental Angiogenic Lipid Factor on Revascularization of Autotransplanted Spleen in Dogs

Abstract: Since the turn of the century, studies have been carried out showing that the omentum contains a factor which enhances revascularization of ischemic tissues. This study was conducted for a period of 3 months and was designed to evaluate the effect of an omental lipid fraction on neovascularization of autotransplanted spleen chips in dogs. Twelve dogs underwent splenectomy and autotransplantation of 5 splenic chips into an omental pouch. In 4 dogs, the splenic chips were immersed in omental angiogenic lipid fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
1
10
0
1
Order By: Relevance
“…In mongrel dogs, we found that autotransplanted spleen chips need at least 2.5-4 months to regenerate; until this point they behaved as an asplenic or hyposplenic state. 4,6,13 In this study, we found that spleen autotransplantation in mice restored normal function in this regard within 6 weeks.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In mongrel dogs, we found that autotransplanted spleen chips need at least 2.5-4 months to regenerate; until this point they behaved as an asplenic or hyposplenic state. 4,6,13 In this study, we found that spleen autotransplantation in mice restored normal function in this regard within 6 weeks.…”
Section: Discussionsupporting
confidence: 56%
“…13,16 The omentum could help angiogenesis, probably by vascular endothelial growth factor (VEGF) expressed mainly by omental adipocytes, rather than stromal-vascular cells. 15 Sasaki demonstrated by scan- ning electron microscopy that neovascularization in rat splenic autografts transplanted into the omentum is classified into four steps: 1) capillarization in the connective tissue surrounding the degenerated autograft, 2) connection of blood vessels between the still-surviving splenic cords and capillaries, 3) rebuilding of splenic sinuses, and 4) remodeling of regenerated blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Prevascularization of the patch and rapid anastemosis of the patch vasculature with host myocardial vessels would ensure the rapid engraftment and integration of the patch into the infarcted myocardium. Implantation on omentum for inducing vasculogenesis in tissue explants was previously explored (16)(17)(18). Here, we have used the omentum for prevascularization and cardiac tissue engineering given that this tissue is enriched with blood vessels.…”
Section: Scar) (A and B) Nonpaced (Spontaneous) Electrical Signals Rmentioning
confidence: 99%
“…9,10 Our study compared the multiple organ-chip model to a single liver, kidney, spleen, and intestine chip technique. The histological data revealed no difference: The spleen appeared to be the most preserved organ in our experimental model, as it had a recognizable structure without significant damage.…”
Section: Discussionmentioning
confidence: 99%